Contusion expansion, low platelet count and bifrontal contusions are associated with worse patient outcome following traumatic brain injury-a retrospective single-center study - Andersson, Alice S.; Hossain, Iftakher; Marklund, Niklas (Springer, 2026)
Background
Cortical contusions are common in moderate-severe traumatic brain injury (TBI). Cortical contusions often expand, potentially causing neuro-worsening several hours to days post-trauma. While contusion expansion (CE) may affect outcome, potential clinical and radiological markers that can predict CE have been insufficiently explored. In the present single-center retrospective observational cohort study, we evaluated clinical outcome by the Glasgow Outcome Scale extended (GOSE) scale and evaluated risk factor for CE.
Method
Adult TBI patients > 18 years of age, and of all injury severities, were included. Main variables of interest were low platelet count, defined as < 150 × 109/L, presence of bifrontal contusions and CE, defined as absolute contusion volume increase in cm3. Factors associated with CE and clinical outcome according to GOSE were analyzed.
Results
Between 2012–2022, 272 patients were included. Contusion size on admission correlated positively with CE, as did the Marshall and Rotterdam radiological classification scores. Bifrontal contusions were significantly larger at admission, experienced larger CE, and had a worse outcome than contusions in other locations. Patients with a platelet count < 150 × 109/L experienced a greater volume CE and had a worse outcome when compared to patients with a normal platelet count. In a multivariate analysis, CE remained significantly associated with a poor outcome six months post- injury.
Conclusion
Contusion volume at admission, Marshall CT classification and Rotterdam CT score, positively correlated to CE. Bifrontal contusions and a platelet count < 150 × 109/L were associated with CE, and a poor clinical outcome. Large CE volumes were associated with a worse clinical outcome, and CE was per se associated with outcome in a multivariate analysis. Management of these risk factors for CE in the acute post-injury setting may be needed to attenuate contusion expansion and to improve clinical outcome in TBI patients suffering from cortical contusion injuries.